2017
DOI: 10.3389/fphys.2017.00267
|View full text |Cite
|
Sign up to set email alerts
|

FAM20A Gene Mutation: Amelogenesis or Ectopic Mineralization?

Abstract: Background and objective: FAM20A gene mutations result in enamel renal syndrome (ERS) associated with amelogenesis imperfecta (AI), nephrocalcinosis, gingival fibromatosis, and impaired tooth eruption. FAM20A would control the phosphorylation of enamel peptides and thus enamel mineralization. Here, we characterized the structure and chemical composition of unerupted tooth enamel from ERS patients and healthy subjects.Methods: Tooth sections were analyzed by Scanning Electron Microscopy (SEM), Energy Dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(72 reference statements)
2
11
0
4
Order By: Relevance
“…Furthermore, the patients were tested for alterations in their blood (calcium, ionized calcium, phosphate, parathyroid hormone, vitamin D (25OH and 1,25(OH)2), alkaline phosphatase and creatinine) and urine collected during 24 hours (calcium, phosphate, creatinine, osmolarity, specific gravity and glomerular filtration rate). Gingival tissues, teeth and pericoronary tissues removed for the purpose of oral rehabilitation were evaluated by classic H&E staining, and by screening electron microscopy (SEM) as published previously 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the patients were tested for alterations in their blood (calcium, ionized calcium, phosphate, parathyroid hormone, vitamin D (25OH and 1,25(OH)2), alkaline phosphatase and creatinine) and urine collected during 24 hours (calcium, phosphate, creatinine, osmolarity, specific gravity and glomerular filtration rate). Gingival tissues, teeth and pericoronary tissues removed for the purpose of oral rehabilitation were evaluated by classic H&E staining, and by screening electron microscopy (SEM) as published previously 17 .…”
Section: Methodsmentioning
confidence: 99%
“…S2). Additional studies (81) have shown that erupted enamel from an ERS patient was mostly comprised of smaller and less organized enamel crystals, compared with normal enamel, which was reported to cover a thin "inner-most" layer of prismatic enamel adjacent to the DEJ. The enamel phenotypes observed in our S16A mutant mice that lack AMELX phosphorylation are quite similar to the reported enamel phenotypes in humans affected by mutations in a key kinase that is believed to play a critical role in amelogenesis.…”
Section: Amelogenin Phosphorylation Is Essential For Enamel Formationmentioning
confidence: 99%
“…Lignon et al 21 , utilizaron la microscopía electrónica de barrido (MEB) y métodos fisicoquímicos en pacientes con mutaciones FAM20A, constataron cristales pequeños y pocos compactados en todo el espesor del esmalte dental. La superficie del esmalte mostraba un patrón globular a nivel ultraestructural similar a la observada en la mineralización ectópica de tejidos blandos.…”
Section: Fenotipo Bucodentalunclassified
“…Análisis realizado por microscopia electrónica a transmisión revela que la talla de las mineralizaciones ectópicas gingivales es variable, en ocasiones únicas o fusionadas que pueden presentar un diámetro de 1 µm hasta 100µm. Esta característica sugiere que estas calcificaciones se fusionan con el tiempo 21 .…”
Section: Fenotipo Gingivalunclassified
See 1 more Smart Citation